Jared Diamond, James A. Robinson (Eds.): Natural Experiments of History. Cambridge (Massachusetts), The Belknap Press of Harvard University Press, 2010, 278 págs. - Bouso Bouso, Natalia (Investigaciones de Historia Económica, 2019)
Sin resumen